New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America - Ale-Rocha, Rosaly (Zootaxa, 2017)
Eleven new species of Neohybos Ale-Rocha & Carvalho from South America are described: N. aberrans sp. nov. (Brazil); N. adustus sp. nov. (Brazil, Peru); N. annulatus sp. nov. (Brazil); N. arcuatus sp. nov. (Brazil); N. elongatus sp. nov. (Brazil); N. hirsutus sp. nov. (Brazil); N. izabelensis sp. nov. (Brazil); N. lautus sp. nov. (Brazil); N. neblinensis sp. nov. (Brazil); N. pectinatus sp. nov. (Colombia, Peru); and N. ramosus sp. nov. (Brazil). Neohybos luridus (Bezzi) is recorded for the first time from Colombia. A key to the South American species is given.